2011
DOI: 10.13171/mjc.1.2.2011.18.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Telon dye removal from Cu(II)-containing aqueous media using p-diphosphonium organo-montmorillonite

Abstract: Ion-exchange of montmorillonite with para-bis(triphenyl phosphonium methylene)-benzene ions (p-TPhPMB) provided an organo-montmorillonite adsorbent with improved affinity towards Telon dyes. Adsorption tests applied to Telon-red and Telon-blue in the presence of Cu(II) cations revealed a significant increase in the maximum adsorption capacity from ca. 11-26 for the starting clay mineral to ca. 110-160 mg.g-1 after intercalation. This improvement was attributed to increases in both the organophilic character to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The chemical composition of purified bentonite was found to be as follows: 64.7% SiO 2 , 18.1% Al 2 O 3 , 0.95% Fe 2 O 3 , 2.66% MgO, 0.8% K 2 O, 0.61% CaO, 0.2% TiO 2 , 1.43% Na 2 O, 0.05% As, and 10.0% loss on ignition [16][17][18][19].…”
Section: Bentonite Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of purified bentonite was found to be as follows: 64.7% SiO 2 , 18.1% Al 2 O 3 , 0.95% Fe 2 O 3 , 2.66% MgO, 0.8% K 2 O, 0.61% CaO, 0.2% TiO 2 , 1.43% Na 2 O, 0.05% As, and 10.0% loss on ignition [16][17][18][19].…”
Section: Bentonite Samplementioning
confidence: 99%
“…The mineralogical analysis showed that the native crude clay mineral predominantly contains montmorillonite (86 wt.%). The clay composition also contains quartz (10%), cristoballite (3.0%) and beidellite (less than 1%) [18,19].…”
Section: Bentonite Samplementioning
confidence: 99%